Political economy perspective of mining policy: a case study on rent seeking in clear and clean regulation of coal mining in indonesia (2009-2014) - Arwanto, Bambang (JURNAL MANAJEMEN, 2018)
Since the New Order era mining policy is strongly tended to be political for the fact that this sector is highly promising. The case on Clear and Clean mechanism was full of potency on rent-seeking with the modus of various regulation misuse. Every spot of rent-seeking in this case has provided different opportunity of manipulation. The Clear and Clean case also shown about the strength of central government against local government. The local government was considered as the party that resembles the business owner so it was their duty to save the asset. The strength of patron-client in clear and clean policy was mainly proven by the fact of the appearance of Individual triangle alliance as a broker. This also explained that woman and paranormal as third person was strongly very influential in lobbying between the interest business owners and bureucrates. The result of research also reconfirmed about the strength of patron-client model. This model was indicated by the existance of strength informal actors that penetrated the environment of formal bureaucracy. Strength of those informal actors was the main key of access business owner in the rent-seeking network and circle in different spots.